Neural correlates of working memory and its association with metabolic parameters in early-treated adults with phenylketonuria - Stephanie Abgottspon; Raphaela Muri; Shawn E. Christ; Michel Hochuli; Piotr Radojewski; Roman Trepp; Regula Everts (NeuroImage: Clinical, 2022)
Background: Phenylketonuria (PKU) is an inborn error of metabolism affecting the conversion of phenylalanine (Phe) into tyrosine. Previous research has found cognitive and functional brain alterations in individuals with PKU even if treated early. However, little is known about working memory processing and its association with task performance and metabolic parameters. The aim of the present study was to examine neural correlates of working memory and its association with metabolic parameters in early-treated adults with PKU. Methods: This cross-sectional study included 20 early-treated adults with PKU (mean age: 31.4 years ± 9.0) and 40 healthy controls with comparable age, sex, and education (mean age: 29.8 years ± 8.2). All participants underwent functional magnetic resonance imaging (fMRI) of working memory to evaluate the fronto-parietal working memory network. Fasting blood samples were collected from the individuals with PKU to acquire a concurrent plasma amino acid profile, and retrospective Phe concentrations were obtained to estimate an index of dietary control. Results: On a cognitive level, early-treated adults with PKU displayed significantly lower accuracy but comparable reaction time in the working memory task compared to the control group. Whole-brain analyses did not reveal differences in working memory-related neural activation between the groups. Exploratory region-of-interest (ROI) analyses indicated reduced neural activation in the left and right middle frontal gyri and the right superior frontal gyrus in the PKU group compared to the control group. However, none of the ROI analyses survived correction for multiple comparisons. Neural activation was related to concurrent Phe, tyrosine, and tryptophan concentrations but not to retrospective Phe concentrations. Conclusion: In early-treated adults with PKU, cognitive performance and neural activation are slightly altered, a result that is partly related to metabolic parameters. This study offers a rare insight into the complex interplay between metabolic parameters, neural activation, and cognitive performance in a sample of individuals with PKU.